2019
DOI: 10.3390/jcm8040473
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Maternal-Foetal Parameters on Concentrations of Zonulin and Calprotectin in the Blood and Stool of Healthy Newborns during the First Seven Days of Life. An Observational Prospective Cohort Study

Abstract: Background: It can be hypothetically assumed that maternal and perinatal factors influence the intestinal barrier. Methods: The study was conducted with 100 healthy, full-term newborns breastfed in the first week of life, with similar analyses for their mothers. Zonulin and calprotectin levels were used as intestinal permeability markers. Results: The median (range) zonulin concentrations (ng/mL) were in mothers: serum, 21.39 (6.39–57.54); stool, 82.23 (42.52–225.74); and newborns: serum cord blood, 11.14 (5.8… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
0
7

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 14 publications
(36 citation statements)
references
References 82 publications
1
25
0
7
Order By: Relevance
“…In our clinic, a previous study [29] found that maternal-foetal factors, such as caesarean section, antibiotic therapy during pregnancy and body mass index (BMI) increase > 5.7 during pregnancy may have impacted on increases in intestinal barrier permeability in newborn children up to seven days of age.…”
Section: Introductionmentioning
confidence: 93%
See 2 more Smart Citations
“…In our clinic, a previous study [29] found that maternal-foetal factors, such as caesarean section, antibiotic therapy during pregnancy and body mass index (BMI) increase > 5.7 during pregnancy may have impacted on increases in intestinal barrier permeability in newborn children up to seven days of age.…”
Section: Introductionmentioning
confidence: 93%
“…In the previous stage, the intestinal-barrier status was assessed in mothers before delivery and in newborns in the first week of life. In the presented second stage of the study, based on the same cohort, the state of the intestinal barrier in children between one and twenty-four months of age was assessed [29].…”
Section: Subject Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…These observations are backed by studies assessing immunological markers such as calprotectin in this group of patients [81,82]. In addition, these markers are dependent on maternal-fetal factors, such as antibiotic therapy or BMI changes during pregnancy, mode of delivery, and feeding patterns [75]. For this reason, in order to fully assess the causal relationship between the microbiota and the function of the immune system with relation to symptoms of infantile colic, a multifactorial analysis should be performed, which was not performed in the works described in this systematic review.…”
Section: Discussionmentioning
confidence: 98%
“…On the other hand, if breast milk microbiota are affected by intrapartum antibiotics, in some cases, the beneficial effect of breast milk on the gut microbiome may be unfavourably altered [74]. Importantly, most authors did not report variables that may shape gut microbiota and intestinal permeability in newborns, e.g., mode of delivery, weight gain during pregnancy, antibiotic therapy during pregnancy and labor [75], which all may affect colicky behaviour. In addition, a body of evidence exists that links infantile colic with caffeine consumption [76] and smoking [77,78], as well as consumption of allergenic products [79].…”
Section: Discussionmentioning
confidence: 99%